KESEHATAN BIBIT JABON MERAH (Anthocephalus macrophyllus) DI BALAI PERHUTANAN SOSIAL DAN KEMITRAAN LINGKUNGAN (BPSKL) BANJARBARU KALIMANTAN SELATAN - Salwiyyah Salwiyyah; Susilawati Susilawati; Adistina Fithria (Universitas Lambung Mangkurat, 2020)
Red Jabon (Anthocephalus macrophyllus) is one of the plant that grows quickly. Planting of red Jabon can not be separated from attacks by pests and diseases in the nursery.The purpose of this riset was to determine the causes and types of damage that attacked of red Jabon seeds and to determine the intensity of the attacks of red Jabon seeds. research method uses the EMAP (Environmental Monitoring and Assessment Program) simple random sampling with a comparison of the value of the codefication to damage of the plants, to get the category a healthy seeds or sick seeds. The results showed that of the total number of live seedlings of red Jabon, 293 seeds were found to be unhealthy. while 159 seeds were healthy, and 28 seeds were killed.This shows that there is damage by pests and diseases in red Jabon seeds which are marked as leaves to become holes and yellow leaves.The number of seeds was attacked by pests and diseases as many as 246 seeds with a severity level of 20-29%.The severity of all pest and disease attacks is still low because the damage does not reach 50%.Keywords: Anthocephalus macrophyllus, pests, diseases, intensity of leaf attack